Unusual presentation of anomalous origin of the right pulmonary artery from the ascending aorta: case report - Mohamed Elhudairy; Naif Alkhushi; Osman Al-Radi; Khadijah Maghrabi; Gaser Abdelmohsen (The Egyptian Heart Journal)
Abstract Background Anomalous origin of the right pulmonary artery (AORPA) from the ascending aorta is a rare congenital anomaly, representing approximately 0.12% of all congenital heart defects. Early diagnosis and timely intervention are essential to prevent severe complications such as heart failure and pulmonary vascular disease. Case presentation We report a case of a full term neonate presented with respiratory distress and cyanosis. Echocardiography revealed an anomalous right pulmonary artery (RPA) origin from the ascending aorta, a large patent ductus arteriosus (PDA) with right-to-left shunt, and moderate tricuspid regurgitation. Despite initial management with prostaglandin E1 (PGE1) infusion, discontinuation of the drug led to clinical deterioration characterized by severe metabolic acidosis and low cardiac output syndrome. Resuming PGE1 infusion stabilized the patient’s hemodynamics and improved systemic blood flow, allowing for successful surgical repair. Conclusion In cases of AORPA associated with aortic arch flow reversal, pulmonary hypertension, and inadequate interatrial communication, maintaining PDA patency with PGE1 infusion until surgical repair is critical for survival. The right-to-left flow across the PDA counteracts the steal from the aorta and decompresses the right ventricle, preventing right ventricular failure and maintaining systemic blood flow. Graphical abstract